Numerical study of magnetized Powell–Eyring hybrid nanomaterial flow with variable heat transfer in the presence of artificial bacteria: Applications for tumor removal and cancer cell destruction - Tang, Tao-Qian; Rooman, Muhammad; Shah, Zahir; Khan, Saima; Vrinceanu, Narcisa; Alshehri, Ahmed; Racheriu, Mihaela (Frontiers in Materials, 2023)
This investigation determined the effectiveness of an exterior magnetic field on bacteria enclosed by thousands of magnetite nanoparticles. Variable thermal conductivity and Joule heating were used in the interstitial nano liquid in which artificial bacteria were swimming in a biotic cell. The unsteady motions of a Powell–Eyring fluid in two dimensions were assumed. The porous extending wall was used as a bent surface shape. To convert the governing non-linear PDEs into non-linear ODEs, suitable transformations were exploited. The homotopy analysis technique (HAM) was utilized to resolve the semi-analytical results of non-linear ODEs. Plots were utilized to investigate the impact of significant parameters of velocity distribution, temperature profile, bacterial density field, nutrient concentration field, skin friction, Nusselt number, and nutrient concentration density. Clinical disease has shown that daring tumors have reduced blood flow. The results of this study showed that augmenting the values of unsteady parameters improved the blood velocity profile. The velocity distribution decreased for higher magnetite volume fraction values, as well as porosity and magnetic parameters. As the concentration of magnetite nanoparticles increased, so did the blood temperature distribution. As a result, the immersion of magnetite nanoparticles improved the physical characteristics of the blood. These findings also demonstrated that magnetic parameters and Eckert number play an essential role in increasing heat transfer rates.